The Perceptions of Junior High School Teachers in West Nias Regency towards the Implementation Independent Curriculum in 2023 - Ibrahim; Mariyance Prida Mehaga; Ade Ros Riza; Alan Alfiansyah Putra Karo Karo; Froilan D Mobo (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The article was to find out how enthusiastic Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) teachers in West Nias district about the process of implementing learning using the independent curriculum in 2023. The researchers used survey approach in quantitative descriptive investigations. The data collection method used questionnaire, and the data analysis used descriptive statistics with percentages. Quota sampling was used to determine the population in this study, which totaled 40 PJOK teachers in West Nias District. The number of samples was based on the number of people visited by the researchers of 40 PJOK teachers in West Nias District. The instrument used a reliability level of 0.975 which is relatively high. The result showed that the teachers with keywords have moderate perceptions of the implementation of independent curriculum learning in West Nias Regency in 2023. The results of distributing questionnaires at the SMP level in West Nias Regency have a percentage of 5% or 2 teachers have categories very positive, the percentage of 3% or 1 teacher has a positive category, the percentage of 80% or 32 teachers has a moderate category, the percentage of 12% or 5 teachers has a negative category and the percentage of 0% or 0 teachers has a very negative category. This indicates that the opinion of PJOK teachers regarding the implementation of learning using the independent curriculum at the West Nias District Middle School level in 2023 is in the moderate category, this can be seen from the highest percentage results which state that the percentage of 80% or 32 teachers is in the moderate category. Keywords: Perceptions of junior high school teachers, independent curriculum implementation